On the Resilience of Opportunistic Networks against DoS Attacks - Afzali, Sanaz; Udugama, Asanga; Förster, Anna; Fischer, Mathias (Electronic Communications of the EASST, 2021)
Opportunistic Networks (OppNets) enable contact-based networking and service provisioning when no infrastructure exists, e.g., in disaster areas. In such sensitive scenarios, maintaining their availability is important, but most existing work on OppNets mainly assume fully cooperative and thus not malicious nodes. In this paper, we study the impact of different flavors of low-intensity Denial of Service (DoS) attacks on OppNets, which are hard to detect and to counter. Our results indicate that low-rate DoS and black hole attacks as a special case of DoS, seem to have a huge impact on the packet delivery ratio and the delivery delay of an OppNet.